Programming collective intelligence : building smart web 2.0 applications - Segaran, Toby (Sebastapol [Calif.] : O'Reilly, 2007)
Provides information on building Web 2.0 applications that have the capability to mine data created by Internet applications.
Includes index.
Keywords: Information technology -- Social aspects -- Programming; Internet programming